Gyre and gimble: a maximum‐likelihood replacement for Patterson correlation refinement. Issue 4 (12th April 2018) - McCoy, Airlie J.; Oeffner, Robert D.; Millán, Claudia; Sammito, Massimo; Usón, Isabel; Read, Randy J.
Abstract : Maximum‐likelihood rigid‐body refinement can be carried out to improve oriented models before the translation‐function step of molecular replacement. Abstract : Descriptions are given of the maximum‐likelihood gyre method implemented in Phaser for optimizing the orientation and relative position of rigid‐body fragments of a model after the orientation of the model has been identified, but before the model has been positioned in the unit cell, and also the related gimble method for the refinement of rigid‐body fragments of the model after positioning. Gyre refinement helps to lower the root‐mean‐square atomic displacements between model and target molecular‐replacement solutions for the test case of antibody Fab(26‐10) and improves structure solution with ARCIMBOLDO_SHREDDER .